THE ESSENCE OF RESOURCE POTENTIAL AND EFFICIENCY IN SERVICE ENTERPRISES OF THE BUKHARA REGION - D. D. Alimova (Journals Park Publishing, 2024)
The rapid development of service sectors in our republic, based on the effective development of market relations, primarily depends on increasing the resource potential of enterprises. Our country has its own policy in the field of economy, which provides for the implementation of a complex of measures aimed at the development of modern service sectors and the effective use of existing resources as factors for achieving it. The development of the service sector is economically more effective than production, since the organization of initial activities in the service sector requires less investment and is characterized by a high rate of turnover of financial resources.